Excessive copper impairs intrahepatocyte trafficking and secretion of selenoprotein P - Schwarz, Maria; Meyer, Caroline E.; Löser, Alina; Loßow, Kristina; Hackler, Julian; Ott, Christiane; Jäger, Susanne; Mohr, Isabelle; Eklund, Ella A.; Patel, Angana A. H.; Gul, Nadia; Alvarez, Samantha; et al. (Nature Communications, 2023)
Selenium homeostasis depends on hepatic biosynthesis of selenoprotein P (SELENOP) and SELENOP-mediated transport from the liver to e.g. the brain. In addition, the liver maintains copper homeostasis. Selenium and copper metabolism are inversely regulated, as increasing copper and decreasing selenium levels are observed in blood during aging and inflammation. Here we show that copper treatment increased intracellular selenium and SELENOP in hepatocytes and decreased extracellular SELENOP levels. Hepatic accumulation of copper is a characteristic of Wilson’s disease. Accordingly, SELENOP levels were low in serum of Wilson’s disease patients and Wilson’s rats. Mechanistically, drugs targeting protein transport in the Golgi complex mimicked some of the effects observed, indicating a disrupting effect of excessive copper on intracellular SELENOP transport resulting in its accumulation in the late Golgi. Our data suggest that hepatic copper levels determine SELENOP release from the liver and may affect selenium transport to peripheral organs such as the brain.
Online veröffentlicht: 13. Juni 2023
Gesehen am 08.12.2023